A Gel Consistency Test for Eating Quality of Rice - Cagampang, Gloria B.; Perez, Consuelo M.; Juliano, Bienvenido O. (Wiley, 1973)
A rapid, simple test, complementary to the test for amylose content, was developed based on the consistency of a cold 4.4% milled‐rice paste in 0.20 N‐KOH. Consistency is measured by the length in a test tube of the cold gel held horizontally for 0.5 or 1 h. The consistency values are correlated with amylograph setback viscosity and can differentiate into three consistency types–low, medium, and high–even rice samples of similar amylose contents as long as they are between 24 to 30%.